Neural mechanisms of implicit cognitive reappraisal: Preceding descriptions alter emotional response to unpleasant images. (7th April 2017) - Wang, Hai-Yang; Xu, Guo-Qing; Ni, Ming-Fei; Zhang, Cui-Hong; Sun, Xiao-Pei; Chang, Yi; Zhang, Bing-Wei
Highlights: To investigate the neural basis of implicit reappraisal in healthy participants. Activity in prefrontal and temporal areas increased during implicit reappraisal. Activity in amygdala decreased during implicit reappraisal. Negative coupling between prefrontal regions and the amygdala. Abstract: The importance of reappraising negative events to reduce negative emotional responses has been widely acknowledged. However, most neuroimaging studies have explored the neural mechanisms of deliberate and intentional reappraisal, while little is known about the neural correlates of reappraisal that occurs outside of one's awareness. Electrophysiological studies suggest that precedent neutral descriptions could implicitly reduce neural responses to unpleasant images. To investigate the neural mechanism underlying implicit reappraisal, functional magnetic resonance imaging was conducted on 25 participants while they passively viewed unpleasant images that were previously neutrally/positively or negatively described. Increased activity in prefrontal areas including the dorsolateral and dorsomedial prefrontal cortices, lateral orbitofrontal cortex, and temporal cortex, and decreased activation in the amygdala was observed—similar to the pattern reported in deliberate emotion regulation—when unpleasant images were preceded by neutral/positive versus negative descriptions. Functional connectivity analysis revealed significant negative couplings between prefrontal regions and the amygdala. These findings suggest that implicit reappraisal recruits prefrontal regions to change semantic representations in the temporal cortex, in turn modulating the emotional response of the amygdala.